Ultrafast Electron Dynamics at the Water‐Modified InP(100) Surface - Jonathan Diederich; Agnieszka Paszuk; Isaac Azahel Ruiz Alvarado; Marvin Krenz; Mohammad Amin Zare Pour; Diwakar Suresh Babu; Jennifer Velazquez Rojas; Christian Höhn; Yuying Gao; Klaus Schwarzburg; David Ostheimer; Rainer Eichberger; et al. (Advanced Materials Interfaces)
Abstract The interaction of water molecules with semiconductor surfaces is relevant to various optoelectronic phenomena and physicochemical processes. Despite advances in fundamental understanding of water‐exposed surfaces, the detailed time‐ and energy‐resolved behavior of excited electrons remains largely unexplored. Here, the effects of water exposure on the near‐surface electron dynamics of phosphorus‐terminated p(2×2)/c(4×2)‐reconstructed indium phosphide (100) (P‐rich InP) are studied experimentally and matched to theoretical calculations. The P‐rich InP surface, consisting of H‐passivated P‐dimers, serves as a model for other P‐containing III‐V semiconductors such as gallium phosphide (GaP) or aluminum indium phosphide (AlInP). Electron dynamics near the surface are probed with femtosecond resolution using time‐resolved two‐photon photoemission (tr‐2PPE), a pump‐probe spectroscopic technique. Pulsed water exposure preserves electronic states and significantly increases lifetimes at the conduction band minimum (CBM). Density‐functional theory (DFT) calculations attribute these findings to suppression of surface vibrational modes in the top P‐layer by water exposure, reducing electronic transition probabilities of near‐band‐gap surface states. The results suggest that many near‐surface state lifetimes reported in ultra‐high vacuum may change significantly upon electrolyte exposure. These states may thus contribute more strongly to surface reactions than traditionally assumed. Demonstrating this effect for the technologically relevant P‐rich InP surface opens new opportunities in this underexplored area of surface electrochemistry.